IC security and quality improvement by protection of chip backside against hardware attacks. (September 2018) - Amini, E.; Beyreuther, A.; Herfurth, N.; Steigert, A.; Muydinov, R.; Szyszka, B.; Boit, C.
Abstract: In this work, a protection structure for the silicon chip backside will be presented, which is a protective TiO2 -Ti-TiO2 layer stack with an angular dependent reflectivity. It uses a selected p-n junction as the light emitter and other junctions as photodetectors of the light reflected in various angles inside the silicon. The measurement of this structure highlights strong angle-dependent reflectivity for the light reflected off the backside of the chip. Detecting these photocurrents indicates whether the IC backside is subject to a hardware attack that violates the backside layer integrity, like FIB, or preparative damage of the layer. Creating a pattern of photocurrent ratios when the IC is running can signal the IC whether such physical attacks from the backside have occurred. For this protection concept, there is no need to add additional masks or circuitry of the IC, since it could use the drain or source junctions of transistors already available.